Childhood‐Grounded Explanations for Personal Troubles: Social Problems Work in Radio Counseling. Issue 2 (5th August 2019) - Thell, Nataliya
Abstract : This paper examines how images of unfortunate childhoods are invoked to make sense of psychological problems in adulthood. I use conversation analysis and membership categorization analysis to study a Swedish radio program in which a psychotherapist talks to people about their personal troubles. The findings suggest that, on one hand, the image of an unfortunate childhood was used as an explanatory framework for individuals' problematic experiences. On the other hand, the childhood‐grounded reasoning, applied to individual cases, illustrated the explanatory framework and reaffirmed it as a commonsense way of reasoning about personal troubles.